(untitled) (Physical Education, Health and Social Sciences, 2025)
Objective: To quantify the early burden of six acute complications of prematurity—respiratory distress syndrome (RDS), patent ductus arteriosus (PDA), sepsis/meningitis, retinopathy of prematurity (ROP), intraventricular haemorrhage (IVH) and necrotising enterocolitis (NEC)—and to explore their association with basic demographic and perinatal factors in a Pakistani neonatal unit. Methods: This descriptive study enrolled 150 consecutive premature neonates (gestation < 37 weeks; age 1–24 h) admitted to the Department of Pediatrics, Imran Idrees Teaching Hospital, Sialkot, over six months. Infants with major congenital malformations or who died before 36 weeks’ post-menstrual age were excluded. A pre-validated proforma captured sex, birthweight, gestational age, residence, delivery mode and five-minute Apgar score. Standardised examination plus targeted imaging and laboratory tests identified each complication. Data were analysed with SPSS 26.0; means ± SD described continuous variables, frequencies and percentages described categorical variables, and χ² or Fisher’s exact tests assessed associations (p ≤ 0.05). Results: Mean post-natal age was 12.1 ± 7.6 h; mean birthweight 1.50 ± 0.42 kg; mean gestation 31.7 ± 2.6 weeks. Girls slightly outnumbered boys (53 % vs 47 %). Deliveries were 54 % vaginal, 37 % caesarean and 9 % assisted with episiotomy; 55 % of families were urban. RDS was most common (69/150, 46 %), followed by PDA (35 %), sepsis/meningitis (32 %), ROP (17 %), IVH (15 %) and NEC (6 %). Stratified analysis showed no significant links between age at assessment, Apgar category or sex and any complication except sepsis, which occurred more often in females than males (39 % vs 24 %, p = 0.045). Conclusion: Almost half of very-pre-term infants developed RDS within 24 h, and one-third experienced cardiovascular or infectious morbidity. Aside from a female predominance in sepsis, early post-natal or delivery characteristics did not predict complications, underscoring the need for universal surveillance and preventive bundles in resource-limited neonatal intensive-care settings.